2009
DOI: 10.1038/hr.2009.83
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive indices of arterial stiffness in hemodialysis patients

Abstract: The purpose of this study was to evaluate the validity of brachial-ankle pulse wave velocity (baPWV) and the cardio-ankle vascular index (CAVI) as measures of arterial stiffness in hemodialysis (HD) patients. We studied 160 consecutively enrolled HD patients (mean age: 59±13 years; 91 male patients). We measured baPWV and CAVI using a VaSera VS-1000, maximum intima-media thickness (max IMT) of the carotid artery by ultrasonography and blood renal and lipid parameters. As a control, baPWV and CAVI were also mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 28 publications
0
37
0
1
Order By: Relevance
“…Nakamura et al 32) reported that CAVI is closely associated with cystatin C levels, suggesting a significant role of arterial stiffness in renal insufficiency. Ueyama et al 33) also reported that CAVI is high in hemodialysis patients.…”
Section: B Chronic Kidney Disease and Hemodialysis Patientsmentioning
confidence: 95%
See 1 more Smart Citation
“…Nakamura et al 32) reported that CAVI is closely associated with cystatin C levels, suggesting a significant role of arterial stiffness in renal insufficiency. Ueyama et al 33) also reported that CAVI is high in hemodialysis patients.…”
Section: B Chronic Kidney Disease and Hemodialysis Patientsmentioning
confidence: 95%
“…Izuhara et al 25) reported that CAVI is indepen- , Izuhara 25) , Miyoshi 26) , Horinaka 27) [Sairaku 29) ] Intima media thickness of cervical artery Nakamura 24) , Ibata 22) , Takaki 20,28) , Izuhara 25) , Miyoshi 26) , Okura 36) , Sairaku 29) , Horinaka 27) , Hayashi 38) Chronic kidney disease [Mortality rate in patients with hemodialysis] Izuhara 25) , Kobuzono 30) , Takenaka 31) , Nakamura 32) , Ueyama 33) , Satoh-Asahara 36) [Kato 40) ] Cerebral infarction, Dementia Yamamoto 39) Metabolic syndrome Satoh 55) Diabetes mellitus Ibata 22) , Izuhara 25) , Okura 37) Hypertension Kubozono 21) , Okura 37) , Takaki 42) , Kadota 43) Dyslipidemia Takaki 28) Smoking Kubozono 21) , Noike 62) Obstructive sleep apnea syndrome Kumagai 60) dently associated with the severity of coronary atherosclerosis. Recently, Miyoshi et al 26) also supported a correlation between CAVI and coronary atherosclerosis.…”
Section: A Coronary Artery Diseaseunclassified
“…Several studies about chronic kidney diseases described that CAVI correlated with estimated glomerular filtration rate and cystatine C 30) and that CAVI is high in patients undergoing hemodialysis therapy 30,31) .…”
Section: (C) Chronic Kidney Diseases and Maintenance Hemodialysismentioning
confidence: 99%
“…CAVI was measured by the standardized method using a Vasera VS-1000 or VS-1500 (Fukuda Denshi Co., Ltd, Tokyo, Japan) for the Amami and mainland groups, as described previously 27,31,32) . In brief, a cuff was placed on the right and left ankles and the brachium; electrodes for electrocardiography were attached to both upper arms, and a microphone was placed on the sternal angle for phonocardiography.…”
Section: Measurement Of Cavimentioning
confidence: 99%
“…CAVI values are correlated with carotid intima-media thickness 24,25,29,30) . Several studies have revealed a significant relationship between CAVI and the presence and severity of patients with coronary artery disease 31) , hemodialysis 32,33) , and chronic kidney disease 34) . Changes in arterial stiffness following cessation of smoking and application of CAVI have been reported recently 35) ; however, there is little information on the prevalence and geographical variation of high arterial stiffness evaluated by CAVI among the general population.…”
Section: Introductionmentioning
confidence: 99%